The impact of the September 27, 2021, Mw=6.0 Arkalochori (Central Crete, Greece) earthquake on the natural environment and the building stock - Mavroulis, S.; Kranis, H.; Lozios, S.; Argyropoulos, I; Vassilakis, Emm.; Soukis, K.; Skourtsos, Emm.; Lekkas, E.; Carydis, P. (EGU General Assembly 2022, 2022)
On September 27, 2021, an Mw=6.0 earthquake struck the central part of Crete Island (southern Greece) and in particular the Heraklion Region. This event was preceded by an extended foreshock sequence started on early July 2021 and it was followed by an Mw=5.3 aftershock on the following day. Taking into account the spatial distribution of foreshocks and aftershocks and the focal mechanism of mainshock as well as the active faults of the earthquake-affected area, it is evident that the seismic activity is strongly related to the NNE-SSW striking W-dipping faults of the Kasteli fault zone located along the eastern margin of the Neogene to Quaternary Heraklion Basin. The latter has been filled with Miocene to Holocene post-alpine deposits. A field reconnaissance conducted by the authors in the earthquake-affected area shortly after the mainshock revealed that the earthquake-triggered effects comprised mainly rockfalls and slides, as well as ground cracks within or close to landslide zones. These effects were located within the hanging-wall of the KFZ. The affected sites are mainly composed of Miocene deposits and they are characterized by pre-existing instability conditions and high susceptibility to landslides. Far field effects were also observed south of the earthquake-affected area and in particular in the southern coastal part of Heraklion Region. In regards to the spatial distribution of the earthquake-induced building damage, the vast majority was caused in villages and towns founded on Miocene and Holocene deposits of the hanging-wall. Damage was not reported in settlements located in the footwall, which is composed of alpine formations. The dominant building types of the earthquake-affected area comprise: (i) buildings with load-bearing masonry walls made of stones and bricks with clay or lime mortar, mainly constructed without any anti-seismic provisions and (ii) buildings with reinforced-concrete frame and infill walls constructed according to the applicable seismic codes. The former suffered the most severe structural damage including partial or total collapse in many villages founded on post-alpine deposits of the hanging-wall of KFZ. The latter responded satisfactory during the mainshock and were less affected with only non-structural damage including cracking, detachment of infill walls from the surrounding reinforced concrete frame, peeling of concrete and short-column failures. From the abovementioned, it is concluded that the impact of the 2021 Arkalochori earthquake was limited to the hanging-wall of the causative fault zone and in particular to residential areas founded on post-alpine deposits and to slopes highly susceptible to failure within the Heraklion Basin.